Tabel Hidup Lalat Jamur Tiram, Bradysia ocellaris - Rostaman Rostaman (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2023)
Mushroom fly, Bradysia ocellaris Comstock, is a new pest species on oyster mushroom cultivation in Bandung and other districts in West Java. Based on information, the insect widely distributes over countries.The aim of this research was to investigate life table parameters of the insect.Insects were reared in the laboratory using oyster mushroom media as their foods. The result showed that intrinsic rate of population growth () was 0.157, net reproductive rate () 23 individu/generation, and mean generation time (T) 20,5 days. This informartion is important in reproductivity of insect pest in three weeks.